Therapy on the frontline: Reflections on psychoanalysis in humanitarian contexts - Womersley, Gail (My University, 2015)
The lecture briefly outlined the nature of Gail’s work in MSF as a psychologist across five countries : Zimbabwe, Ukraine, South Sudan, Central African Republic (CAR) and the Democratic Republic of Congo (DRC). The main presenting problem of patients in each context will be considered with a view to understanding the various ways in which post-traumatic stress manifests in psychosomatic forms. Case studies of hysterical conversion and other psychosomatic disorders will be examined. The role of psychology in these particular projects and various interventions or treatment methods will be considered. The ethics of doing short term interventions and of doing interventions in under-resourced settings will also be discussed - with a focus on highlighting key theoretical differences between psychoanalysis, psychological debriefing and "psychological first aid" used in humanitarian settings. Does psychoanalysis have a role to play in such contexts?
, Therapy on the Frontline: Reflections on Psychoanalysis in Humanitarian Contexts - Public Lecture, Cape Town, South Africa
Keywords: PTSD trauma MSF (Médecins Sans Frontières) psychosomatic